Influence of BCH and LDPC Code Parameters on the BER Characteristic of Satellite DVB Channels - Jordanova, L.; Laskov, L.; Dobrev, D. (Engineering, Technology & Applied Science Research, 2014)
This article presents the results of a study on the noise immunity of DVB channels when higher-order M-ary APSK modulation schemes and concatenated BCH-LDPC codes are used. Dependencies to determine the probability at the decoder output are given taking into consideration the BCH and LDPC code parameters and the error probability in the communication channel. The influence of the BCH packets length, the BCH code rate, the number of maximum iteration and the parameters of LDPC parity-check matrix on the code efficiency is analyzed. Research of the influence of the concatenated LDPC-BCH code parameters on the radio channel noise immunity is conducted and dependencies to determine the required CNR at the input of the satellite receiver are given.